Viewpoints on how students with autism can best navigate university - Thompson, Craig; Bolte, Sven; Falkmer, Torbjorn; Girdler, Sonya (Informa Healthcare, 2018)
© 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group. Background: Despite recognition of the challenges faced by students with autism spectrum disorders (ASD) there is limited understanding of the barriers and facilitators to participation in major life areas, such as being a university student. Aim/Objective: This research aimed to examine viewpoints on what affects the success of Australian university students with ASD. Material and Method: Q-methodology was used to describe the viewpoints of university students with ASD, their parents and their mentors, on success at university for students with ASD. A total of 57 participants completed the Q-sort. Results/Findings: Three viewpoints emerged; Individualised Support, Contextual Support and Social Support. Conclusions: This study highlighted that supports need to be individualized to the barriers and facilitators faced by Australian students with ASD. Supports also need to be contextualized to the built and social environments of universities. Significance: This study supports the premise that environmental interventions can be effective in facilitating participation in major life areas, such as university education. Peer mentoring for students with ASD may have utility for this group, but should be extended to include social, emotional and psychological support.